Endometriosis - Treatment Methods and the Impact of Physical Activity on Symptoms - Pudełko, Iwona; Klimas, Filip; Zięba, Zuzanna; Potoczek, Adriana; Zatłoka-Mazur, Dorota; Rusiński, Kacper; Kurenda, Kinga; Ząbek, Adam Jan; Lekan, Izabela; Ostrowicz, Klaudia (Quality in Sport, 2025)
Endometriosis is a leading cause of chronic pelvic pain in women of reproductive age, significantly impacting the quality of life. Numerous hypotheses regarding the etiology of endometriosis and its diverse clinical presentation limit the effectiveness of treatment to symptom management, as there is no targeted cure. This review presents the current understanding of how physical activity may contribute to the management of symptoms associated with endometriosis and summarizes the therapeutic strategies employed.